GESTÃO AMBIENTAL PORTUÁRIA NO CONTEXTO DO GERENCIAMENTO COSTEIRO INTEGRADO: UMA PROPOSTA METODOLÓGICA BASEADA NO PORTO DE RIO GRANDE - de Ávila dos Santos, Indira; Armanini Tagliani, Paulo Roberto; Silveira Kitzmann, Dione Iara (Costas, 2022)
Ports play a decisive role in integrating the world economy, which can be assessed by the size of the global merchant fleet, which in the year 2017 was made up of 1.8 million vessels, with a cargo volume of 752, 7 million TEUs. However, port activities usually have significant pressures on the coastal areas where they are located. Such pressures often lead to diffuse environmental impacts, such as air, water, sediment and biota contamination. They also bring socioeconomic, cultural and landscape impacts, leading to conflicts of use with other sectors, such as artisanal fishing and tourism. Such problems demand responses in terms of programs, plans, policies, projects and actions. The environmental control of port activities should therefore go beyond the monitoring of the physical-chemical parameters and consider all dimensions impacted. This paper proposes a monitoring model based on the DPSIR (Drivers, Pressure, State, Impact and Response) model, taking as an example the Rio Grande port in southern Brazil.